PENGARUH KUALITAS PESAN IKLAN SMARTPHONE SAMSUNG TERHADAP NIAT BELI DENGAN CITRA MEREK SEBAGAI VARIABEL PEMEDIASI - Chriswardana Bayu Dewa (Jurnal Manajemen, 2018)
This research aims to examine the effect of quality of the advertising message to the buying intention and mediated by brand image. Subjects are people who use Samsung mobile in Yogyakarta. In this study developed a theoretical mode of the proposed four hypotheses to be tested using Structural Equation Model (SEM) by AMOS software 18. This research was conducted by distributing questionnaires to survey 150 respondents. Respondents were obtained through purposive sampling tehnique, the respondents were selected based on certain goals established researcher. The results of this study show that quality of the advertising message has positive effect to brand image, brand image has positive effect to buying intention, quality of the advertising message has positive effect to buying intention and brand image can partially mediated the positive effect of quality of advertising message toward buying intention.